Bacteraemia in haematopoietic stem cell transplant recipients in a single tertiary referral centre - Nurul Iman P; Ramliza Ramli; Wan Fariza Wan Jamaludin; Shamsul Azhar Shah; Nor Azimah I; S. Fadilah Abd. Wahid (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Bacteraemia is a common and one of the serious complications in haematopoietic stem cell transplantation (HSCT). To date, there are no published data on antibiotic resistance and clinical outcome among HSCT recipients in Malaysia. The aim of the present study was to analyse the prevalence, antibiotic resistance and clinical outcome of bacteraemia in HSCT recipients, within 100 days following transplantation. We retrospectively analysed the prevalence, antibiotic resistance pattern and mortality rate of early bacteraemia among HSCT recipients in a single centre over a 5-year period (2013-2017). Thirty patients of 85 HSCT recipients developed bacteraemia with 40 positive cultures resulting in prevalence of 47% (40/85). Gram negative bacteria (GNB) accounted for 60.5% of total isolates. Enterobacteriaceae and Coagulase negative Staphylococcus (CoNS) were the commonest pathogens isolated. GNB showed a high resistance rate to ciprofloxacin. Only 30% of recipients responded to first line empirical antibiotics for febrile neutropenia (FN). The mortality rate was 13.3% (4/30), of which 50% was attributed to multi-drug resistance (MDR) Acinetobacter and 25% to extended spectrum beta-lactamase (ESBL) Enterobacteriaceae. Bacteraemia is a frequent and life-threatening early complication among HSCT recipients with MDR GNB being the commonest cause of mortality. The high rate of resistance to ciprofloxacin and failure of the first line empirical antibiotics to treat FN calls for a thorough evaluation of the current antibiotic prophylaxis and empirical treatment protocols. These findings have important clinical implications regarding the use and selection of both prophylactic and empiric antibiotic regimens to treat FN.